Do Some People Need Autonomy More Than Others? Implicit Dispositions Toward Autonomy Moderate the Effects of Felt Autonomy on Well‐Being. Issue 1 (10th November 2014) - Schüler, Julia; Sheldon, Kennon M.; Prentice, Mike; Halusic, Marc
Abstract: The present studies examined whether implicit or explicit autonomy dispositions moderate the relationship between felt autonomy and well‐being. Study 1 ( N = 187 undergraduate students) presents an initial test of the moderator hypothesis by predicting flow experience from the interaction of autonomy need satisfaction and autonomy dispositions. Study 2 ( N = 127 physically inactive persons) used vignettes involving an autonomy (un)supportive coach to test a moderated mediation model in which perceived coach autonomy support leads to well‐being through basic need satisfaction. Again, the effects of need satisfaction on well‐being were hypothesized to be moderated by an implicit autonomy disposition. Study 1 showed that individuals with a strong implicit autonomy (but not power or achievement) motive disposition derived more flow experience from felt autonomy than individuals with a weak implicit autonomy disposition. Study 2 revealed that perceived autonomy support from sports coaches, which we experimentally induced with a vignette method, leads to autonomy satisfaction, leading in turn to positive effects on well‐being. This indirect effect held at high and average but not low implicit autonomy disposition. The results indicate that the degree to which people benefit from autonomy need satisfaction depends on their implicit disposition toward autonomy.